Manajemen Risiko Rantai Pasok Getah Pinus Dengan Model House Of Risk - Meidy Rachmalia; Eko Ruddy Cahyadi; Alim Setiawan Slamet (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2022)
Pine resin is one of the demanded products to have proceeded into gondorukem. Gondorukem from Indonesia has a competitive advantage compared to other countries because it is stickier, heat resistant, and has a distinctive aroma so its exports are attractive to other countries. Ensuring the quality and quantity of gondorukem requires a smooth pine resin supply chain. This study aims to determine risk events and risk agents in the supply chain of pine resin that inhibit production, and design strategies to reduce the chance of emerging risks. House of Risk (HOR) is used to determine and apply the priority of risk agents and preventive actions. The study identified a total of 15 risk events and 30 risk agents that affect the quality and quantity of pine resin. Eighteen risk agents are prioritized, three of which are weather conditions, tapping personnel, and tree conditions for designing preventive actions. There are 3 priority preventive actions to handle the risk agent, namely (i) improving and controlling the quality of pine resin from the beginning process, (ii) giving a performance-based incentive and special tariff for a local tapper, and (iii) applying a resin tapping system with biogemme program.